WITHDRAWN: Effects of Additives and Conductors on Properties of Conducting Porous Composite Based on Activated Carbon - Nguyen, Thom Thi; Nguyen, Thu Phuong; Cao, Hong Thi; Vo, Kieu Anh Thi; Nguyen, Thu Trang Thi; Dinh, Mai Thanh Thi; Tran, Dai Lam; Pham, Nam Thi (Communications in Physics, 2020)
Climate change is increasingly clear and threatening to human life. One of the consequences of climate change is the increase of sea level leading to saline intrusion and serious shortage of fresh water. Today, some technologies are used to treat saline water such as Reverse Osmosis technology (RO), Multi-Effect Distillation (MED) technology, and Multi-Stage Discharge Technology (MSF), Electrodialysis (ED) and Capacitive Deionization (CDI). Among them, CDI technology is a technique for energy-saving and economical. The conductive composite electrode based on activated carbon from Tra Bac coconut shell charcoal were fabricated which were used as a electrode for CDI device. In this study, effect of adhesives and conductors on characterization and properties of the materials was investigated. The adhessive of PVDf and conductor of CNTs was chosen. With ratio of AC/CNTs = 9:1, the composite had a specific surface area of BET of about 517 m2/g and pore size of 1.71 nm.